A novel, energy efficient, two stage heap leach process for the extraction and recovery of PGMs - Eksteen, Jacques; Mwase, J.; Petersen, J.; Bradshaw, S.; Akdogan, G.; Mpinga, N.; Snyders, C. (2014)
The platinum group metals (PGMs) and associated minerals are particularly refractory to most traditional direct leach processes. However, the remoteness of many new ore deposits, socio-political risks, the scarcity of skilled labor and constraints on the availability of water and electrical power makes it increasingly more difficult to implement the conventional mill-float-smelt-refine process routes to extract and refine PGMs in remote areas. This paper discusses a process to extract PGMs from low grade ore and concentrate using a sequential stage heap leach process entailing heap bioleaching and high temperature cyanide leaching, and evaluates the feasibility of implementing a carbon-in-pulp process to recover the PGMs from the pregnant leach solution. The heap bioleaching extracts the base metals in an acidic sulfate medium using a mixed culture of thermophiles. After heap bioleaching the heap is reclaimed, rinsed, agglomerated and restacked for high temperature cyanide leaching where the cyanide liquor is directly heated via solar energy in panels. Palladium, gold and platinum are recovered during the cyanide leaching stage. The pregnant leach solution was evaluated for potential carbon-in-pulp adsorption and subsequent elution similar to gold processing. The kinetics of adsorption and elution compared well with gold adsorption and elution.